The Intrapreneur Innovation:Led by Medium and Small Size Companies‘Managers*(Qualitative Research) (2005)
This research is focused on an exploratory study developed with Pymes managers and theirroles as intrapreneurs. Using their leadership to impel innovation into organizations.Looking to determined how Pymes employers incentive into organizations individuals or groupinnovations. Therefore, it is possible to think that managers lead the innovation process, whichis classified gradually according to companies needs in order to improve their competitiveness.Organization must have intrapreneuring and organized culture with flexible structure to generateindividual autonomy. A characteristic is the amount of capital risk needed; that is why it isnecessary encourage their work and their risk tolerance.